2018
DOI: 10.1371/journal.pone.0208410
|View full text |Cite
|
Sign up to set email alerts
|

Establishing trust in HIV/HCV research among people who inject drugs (PWID): Insights from empirical research

Abstract: BackgroundThe establishment of trust between researchers and participants is critical to advance HIV and HCV prevention particularly among people who inject drugs (PWID) and other marginalized populations, yet empirical research on how to establish and maintain trust in the course of community health research is lacking. This paper documents ideas about trust between research participants and researchers amongst a sub-sample of PWID who were enrolled in a large, multi-year community health study of social netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 65 publications
4
37
0
Order By: Relevance
“…This is rather striking but could be attributed to the fact that the outbreak in Athens was recent. This finding is in agreement with previous studies, which found that HIV-infected PWID remain unaware of their serological status for a certain time [20,21,[32][33][34][35][36][37][38]. PWID might not seek HIV testing for a variety of reasons including stigma and discrimination [39][40][41][42][43][44], fear of finding out that they are infected, and their perception of being at low risk for HIV infection [38,45].…”
Section: Discussionsupporting
confidence: 91%
“…This is rather striking but could be attributed to the fact that the outbreak in Athens was recent. This finding is in agreement with previous studies, which found that HIV-infected PWID remain unaware of their serological status for a certain time [20,21,[32][33][34][35][36][37][38]. PWID might not seek HIV testing for a variety of reasons including stigma and discrimination [39][40][41][42][43][44], fear of finding out that they are infected, and their perception of being at low risk for HIV infection [38,45].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to what we observed in this study, data con dentiality is often referred to as a great concern in longitudinal studies in which inclusion of personal identi ers (e.g. name and address) is required in order to assure a proper record linkage and an active follow-up (39,40). This issue, strongly emphasized by women in our study, can be considered a structural barrier potentially resulting from the existing punitive laws and high levels of stigma and discrimination around injecting drug use in Iran (41).…”
Section: Discussionsupporting
confidence: 77%
“…In addition, creating a positive and supportive environment for people was mentioned to be the key to build trust between PWID and the health sectors and therefore help them easily recruit others to research studies. Establishing and maintaining trust has been shown to be fundamental to success in studies of key marginalized populations (39). Peer recruitment methods like RDS, strategies to address the needs of population of interest, and the researchers' developing a good reputation among the studied population have been cited as a few strategies that build trust between researchers and PWID (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, creating a positive and supportive environment for people was mentioned to be the key to build trust between PWID and the health sectors and therefore help them easily recruit others to research studies. Establishing and maintaining trust has been shown to be fundamental to success in studies of key marginalized populations (37). Peer recruitment methods like RDS, strategies to address the needs of targeted population, and the researchers' developing a good reputation among the targeted group have been cited as a few strategies that build trust between researchers and PWID (37).…”
Section: Discussionmentioning
confidence: 99%
“…Data confidentiality is often a great challenge in longitudinal studies in which inclusion of personal identifiers (e.g. name and address) is required in order to assure a proper record linkage and an active follow-up (37,38). This issue, strongly emphasized by women in our study, can be considered a structural barrier potentially resulting from the existing punitive laws and high levels of stigma and discrimination around injecting drug use in Iran (39).…”
Section: Logistics Needed For Cohort Studiesmentioning
confidence: 99%